Effect of proton pump inhibitors on occlusion of lumen-apposing metal stents and rate of endoscopic necrosectomies: a Europe-wide multicenter cohort study - Hamm, Jacob; Busana, Alzbeta; Amanzada, Ahmad; Arlt, Alexander; Asendorf, Thomas; Carswell, Samantha; Denzer, Ulrike; Elsing, Louis; Frost, Fabian; Guilabert, Lucia; Hamesch, Karim; Hollenbach, Marcus; Hegyi, Péter; Kleger, Alexander; Krivinka, Jan; Kunovsky, Lumir; Meinhardt, Christian; Phillip, Veit; Schlosser-Hupf, Sophie; Sirtl, Simon; Welsch, Lukas; Cardinal von Widdern, Julian; Neesse, Albrecht; Ammer-Herrmenau, Christoph; PROTOCOL working group; Beyer, Georg; Dürr, Alicia; Falt, Premysl; Gerst, Christoph; Hoffmeister, Albrecht; Hegyi, Péter; Kohlmann, Thomas; Knoop, Richard; Martinez-Moreno, Belen; Mayerle, Julia; Michl, Patrick; Mollnow, Tobias; Müller, Martina; Pandanaboyana, Sanjay; Petzold, Golo; Rosendahl, Jonas; Schulte, Lucas Alexander; Seifert, Hans; Steiner-Gager, Emanuel; Sulzer, Sabrina; Urban, Ondrej; Zoundjiekpon, Vincent Dansou; Ellenrieder, Volker (Endoscopy, 2025)
Background Lumen-apposing metal stents (LAMS) are widely used to drain walled-off necrosis (WON). LAMS occlusion is a significant clinical problem and identification of risk factors for LAMS occlusion could contribute to novel preventive strategies. A previous study suggested contradictory effects of proton pump inhibitors (PPIs) on occlusion and necrosectomy rates.Methods We conducted a Europe-wide multicenter retrospective cohort study assessing WONs drained by LAMS. The primary aims were to assess the strength of association between PPI intake and LAMS occlusion and necrosectomy rates, respectively. The secondary aim was to assess the strength of association between PPI intake and other LAMS-associated complications. Multiple mixed-effects models were used to control for possible confounding covariates.Results 893 patients with 967 LAMS from 17 centers were included. After excluding incomplete datasets and patients who took PPIs intermittently, 768 LAMS remained. The overall occlusion rate was 28.0 %. Most occlusions occurred within 10 days. Most patients received PPIs continuously (n = 577 vs. no intake n = 191). In patients who did not use PPIs continuously, lower rates of LAMS occlusion (odds ratio [OR] 0.61, P = 0.04) and necrosectomies (incidence rate ratio 0.8, P = 0.006) were observed. A post hoc analysis exhibited a dose- and compound-dependent effect of PPI intake on necrosectomy rate. No increase in other complications in the non-PPI group, such as bleeding events (OR 1.14) were observed. Conclusion PPI intake was associated with higher rates of LAMS occlusion and necrosectomy.